A BINARY INTEGER LINEAR PROGRAMMING MODEL FOR EMPLOYEE SCHEDULING IN A CONVENIENCE STORE: A CASE STUDY IN NAKHON PATHOM - Laisupannawong, Teeradech; Jeenanunta, Chawalit (PATTIMURA UNIVERSITY, 2025)
Convenience stores are workplaces where employees work in shifts. An optimal work schedule for employees is necessary for every convenience store because it enables employees to work more efficiently. This paper considers the employee scheduling of a 24-hour convenience store in Nakhon Pathom. This store divides working hours into three shifts: morning, noon, and night. Each employee is assigned to the same shift for an entire week before rotating to a different shift in the next week. This paper presents a novel binary integer linear programming model for generating an optimal four-week employee schedule for this convenience store. The objective of the proposed model was to prioritize assigning weekend days off to the manager and assistant managers ahead of the regular staff, while adhering to the constraints outlined in the store’s regulations. The proposed model was solved using the CPLEX software to generate an optimal schedule for the 15 employees at this convenience store. The model could find an optimal schedule with a computational time of less than three seconds, where the days off for the manager and assistant managers could all be scheduled on weekends. The proposed model also verified that the current number of employees at the convenience store is the minimum required to create a feasible work schedule, and the store needs to increase its staff by at least two employees if each employee is to work the night shift for at most one week within a four-week schedule period. The proposed model can be a practical tool for generating an optimal employee schedule for this convenience store in real-life scenarios.